The potential for transmission of Coronaviruses via sports equipment; A cricket case study - England, R.; Peirce, N.; Torresi, J.; Mitchell, S.; Harland, A. (International Journal of Sports Medicine, 2021)
A review of literature on the role of fomites in transmission of coronaviruses informed the development of a framework which was used to qualitatively analyse a cricket case study, where equipment is shared and passed around, and identify potential mitigation strategies. A range of pathways were identified that might in theory allow coronavirus transmission from an infected person to a non-infected person via communal or personal equipment fomites or both. Eighteen percent of potential fomite based interactions were found to be non-essential to play including all contact with another persons equipment. Six opportunities to interrupt the transmission pathway were identified, including the recommendation to screen participants for symptoms prior to play. Social distancing between participants and avoiding unnecessary surface contact provides two opportunities; firstly to avoid equipment exposure to infected respiratory droplets and secondly to avoid uninfected participants touching potential fomites. Hand sanitisation and equipment sanitisation provide two further opportunities by directly inactivating coronavirus. Preventing players from touching their mucosal membranes with their hands represents the sixth potential interruption. Whilst potential fomite transmission pathways were identified, evidence suggests that viral load will be substantially reduced during surface transfer. Mitigation strategies could further reduce potential fomites, suggesting that by comparison, direct airborne transmission presents the greater risk in cricket.